2016
DOI: 10.1111/fare.12194
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Enrollment and Engagement of Custodial Grandmothers in a Randomized Clinical Trial of Psychoeducational Interventions

Abstract: The authors used Andersen’s (2008) behavior model to investigate patterns of enrollment and treatment engagement among 343 custodial grandmothers who participated in a randomized clinical trial of three psychosocial interventions:(a) a behavioral parenting program, (b) a cognitive behavioral coping program, or (c) an information-only condition. Treatment completion was superior to that typically found with birth parents, even though the grandmothers and their target grandchildren both had high levels of mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Our previously reported finding of virtually no difference between our three RCT conditions on measures of treatment satisfaction suggests that each condition was appraised by CGMs as being equally credible and beneficial (Smith, Strieder, Greenberg, Hayslip, & Montoro-Rodriguez, 2016). This similarity of appraisals is unsurprising given that all three conditions were meaningfully structured, led by professionals, permitted personal expression in a safe group environment, and provided useful information to participants.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our previously reported finding of virtually no difference between our three RCT conditions on measures of treatment satisfaction suggests that each condition was appraised by CGMs as being equally credible and beneficial (Smith, Strieder, Greenberg, Hayslip, & Montoro-Rodriguez, 2016). This similarity of appraisals is unsurprising given that all three conditions were meaningfully structured, led by professionals, permitted personal expression in a safe group environment, and provided useful information to participants.…”
Section: Discussionmentioning
confidence: 75%
“…At the same time, however, it is noteworthy that only 20% of CGMS failed to attend at least one session which is superior to the 25 to 50% of birth parents scheduled to begin BPT who never attend a single session (Chaco et al, 2016). Nevertheless, identifying strategies for increasing first time attendance at interventions designed for grandfamilies is critical to insure that those most in need actually attend so that treatment effects can be maximized (see Smith et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While program impact findings here cannot necessarily speak to key change processes explaining treatment effects, the emphasis on feeling personally efficacious in setting and implementing goals as well as in future-oriented, solutionbased thinking, and improved emotional functioning (Kim & Franklin, 2015) are potential explanatory mechanisms. In addition, bonding with group facilitators (Kim, 2007) as well as with fellow grandparent caregivers (Hayslip et al, 2015;Smith et al, 2016) may contribute to the positive program outcomes found here.…”
Section: Discussionmentioning
confidence: 87%
“…A majority of studies (n=23, 74%) were exploratory, looking to apply behavioural approaches to identify issues within recruitment/retention by assessing barriers/facilitators to their targets and predisposing characteristics of participants. They explored these barriers/facilitators through qualitative interviews and/or focus groups,27–39 intervention mapping,40 41 surveys/questionnaires,27 31 32 36 42–48 and secondary data analysis 49. These studies identified potential strategies to address these insights, some only suggesting directions for future research while others developed interventions but did not formally evaluate them.…”
Section: Resultsmentioning
confidence: 99%